Enhancement of electrochemical discharge machining accuracy and surface integrity using side-insulated tool electrode with diamond coating. (10th May 2017) - Tang, Weidong; Kang, Xiaoming; Zhao, Wansheng
Abstract: Electrochemical discharge machining (ECDM) is an emerging non-traditional processing technology used to machine electrical non-conductive material like glass and ceramics, by using the electrochemical discharge phenomena around the tool electrode. In the general ECDM drilling process, the gas film forms and electrical discharge appears at both the tool end and the tool sidewall that were exposed to the electrolyte. The undesirable sidewall discharge enlarges the hole entrance diameter and destroys the hole surface integrity. In order to prevent the sidewall discharge, a side-insulated tool electrode with a 4 μ m-thick diamond coating layer was used in ECDM micro-hole drilling. The gas film formation and electrical discharge mostly happened on the tool end due to the insulation layer on the tool sidewall. Experiments showed that, compared with the traditional tool electrode, the side-insulated tool electrode achieves a smaller hole diameter and better surface integrity without an obvious heat affected zone at the hole entrance. Furthermore, the hole diameter nearly remains the same as the machining depth increases from 50 μ m to 500 μ m. The side-insulated electrode has an advantage in enhancing shape accuracy by reducing the taper angle of the micro hole. When the machining depth is 600 μ m, the side-insulated electrode achieves a much smaller hole taper angle ( 3.3 ∘ ) than the traditional tool electrode does ( 6.4 ∘ ).